Investigating the story structure of advice for people of knowledge and intelligence in the language of cat and mouse by Sheikh Baha'i - هلن اولیایی‌نیا (تاریخ ادبیات)
In Sheikh Baha'i's work entitled "Admonitions and advice to the people of knowledge and intelligence in the language of cats and mice", Sheikh Baha'i seeks to eliminate the doubts that exist about Sufism and mysticism and distinguish hypocrisy from mystic spiritual honesty. In order to achieve this goal, Sheikh Baha'i has used all the story-telling techniques that were usual and customary until that time, to create an attractive and worth-reading story from a completely jurisprudential and mystical discussion. Maybe if his theories were listed in a philosophical treatise, it would take the form of a sermon and would not have the attraction that this fictional work has for the reader in its current form, while this work has all the story elements such as conflict between the characters, unraveling, characterization, a special story point of view, tangible human emotions and feelings - of course in the form of an allegory - and a sense of suspense, which is the main factor in following the story by the reader. The author has cleverly woven his theories and instructive points into the fabric of the story so that the reader can be exposed to these points while following the story without feeling bored. This article is an attempt to investigate the story structure of this classic work, which has not been analyzed with new perspectives in literary criticism.